Analysis of Home Security System Based Arduino - Rio Wirawan; Arman Syah Putra; Nurul Aisyah; S Suhardjono (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how to implement a smart security system that will be applied to a smart home concept so that it can help its residents maintain security in the house. Therefore, the proposed system can help the police in securing an area. The method used in this study is to use the SDLC method which consists of 7 stages. The first stage is training. The second stage is the pain requirements. The third stage is there, besides the 4th stage, which is software development. The fifth is testing. The 6th stage is development when the 7th is the president, with the 7 stage, the research will be clear and can find answers to the problems raised. The problem raised in this study is how to create a system that can protect a house from crime, and can protect the surrounding community for the security section, therefore the arrangement of the system made in this study will be able to raise the problem of how to make a system in a smart home. The purpose of this research is how to create a system that can protect a house from crime, and can report to the police if there is a theft in a house.